Osteoporosis treatment gap and risk of refracture: a pilot retrospective study on a cohort of patients referred to a Fracture Liaison Service in Italy - De Mattia, Giammarco; Manca, Maria Laura; Bottai, Vanna; Antognetti, Damiano; Menconi, Agnese; Maffi, Michele; Mosca, Marta; Mazzantini, Maurizio (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionThe timely administration of anti-osteoporotic medications (AOM) to patients with fragility fractures (FF) reduces the imminent refracture risk. European studies found a wide osteoporosis treatment gap, but Italian cohort-based data are lacking.Materials and methodsWe aimed to assess the entity of the osteoporosis treatment gap in an Italian cohort, i.e., the percentage of patients not treated within 2 months from the index fragility fractures (FF) and the time delay in anti-osteoporotic medications (AOM) administration, and its impact on refracture risk. We retrospectively collected the clinical histories of 500 randomly selected osteoporotic patients with FFs referred to our Fracture Liaison Service. We identified those who had AOM prescribed within 2 months from the index FF (“early treatment” group) and those who had not (“untreated” group). Refracture occurrence was retrospectively assessed in both groups, followed by a survival and risk analysis.ResultsForty-one patients were excluded for missing data. Out of 459 patients, 374 (81.5%) received AOM therapy more than 2 months after the index FF, with a median delay of 24 months (IQR 52) (range 3–312; mean 47 months). The log-rank test showed that the “untreated” group was significantly more prone to refracture than “early treatment” (78% vs. 48%, respectively; p = 0.0001). Cox regression revealed a 44% lower probability of refracture in the “early treatment” group.DiscussionIn this study, 81.5% of individuals had their first AOM prescription after a median time of 24 months after the index FF, resulting in higher refracture risk. Preventive strategies to reduce the osteoporosis treatment gap should be implemented.